Descriptive survey of the contextual support for nursing research in 15 countries - Leana R. Uys; Robin P. Newhouse; Arwa Oweis; Xiaokun Liang (AOSIS, 2013)
Background: Global research productivity depends on the presence of contextual factors, such as a doctorally prepared faculty, graduate programmes, publication options, that enablethe conduct and publication of studies to generate knowledge to inform nursing practice. Objectives: The current study aimed to develop and test an instrument that measures the level of contextual support for nursing research within a specific country, allowing comparisons between countries. Method: After development of a 20-item survey with seven factors and 11 criteria based on aliterature review, a quantitative descriptive e-mail survey design was used. Results: Nurse researchers (N = 100) from 22 countries were invited to participate. Theresponse rate was 39% from 15 countries. Ethics approval was obtained by investigators in their country of origin. Results showed wide variation in the level of contextual support. The average total level of support across all countries was 26.8% (standard deviation [SD] = 14.97). The greatest variability was in the area of availability of publishing opportunities (ranging between no suitable journals in a country to over 100). The least variability was in the area of availability of local enabling support (SD = 7.22). This research showed wide differences in the level of contextual support for nursing research. Conclusion: The survey instrument can be utilised as a country assessment that can be used tostrategically plan the building of infrastructure needed to support nursing research. Contextual support for nursing research is an antecedent of strong science. Building infrastructure for nursing science is a priority for global health.